Why Has Computerization Increased Wage Inequality? Information, Occupational Structural Power, and Wage Inequality. Issue 4 (November 2020) - Kristal, Tali
This article offers a new account of rising inequality by providing a new explanation for the observed correlation between computerization and earnings. The argument is that as computers transformed work into a more knowledge-intensive activity, occupations located at critical junctions of information flow have gained greater structural power, and thereby higher wages. Combining occupational measures for location in the information flow based on the Occupational Information Network with the 1979–2016 Current Population Surveys, the analyses reveal a rising wage premium for occupations with greater access to and control of information, independent of the spectrum of skills related to computerization.